Acquisition of English prepositions among Iraqi secondary school students in Kuala Lumpur-Malaysia - Shakir, Hani; Yaseen, Bilal Huri (Australian International Academic Centre, 2015)
The study focuses on the acquisition of English prepositions among students of Iraqi secondary school in Kuala Lumpur, Malaysia. Participants in the study were (20) students all of them at sixth level. The researchers studied the students’ responses to the given test to investigate the problematic prepositions of English language that Iraqi English as foreign language (EFL) learners have in their everyday and academic usage; and investigate the way that EFL Iraqi learners differentiate between using English and Arabic prepositions. The major finding in this study is that the main reason for all the errors is the dominance of the mother tongue (MT) on English language (EL), especially with Arabic language having a syntactic structure when imposed on EL that too with Arabic meaning on EL. The dominance and influence of one’s MT is a major challenge in using the EL in the right way by Iraqi EFL learners. In a subconscious manner, Iraqi EFL learners tend to use or impose their MT’s syntactic, semantic structures and patterns on EL. Arabic and English have different number of prepositions and word-to-word equivalents of prepositions cannot be found between Iraqi Arabic and English Languages. Iraqi EFL learners are influenced by the prepositional system of their MT (Arabic) when they intend to use the prepositions in EL and this leads to errors and lack of idiomaticity. Inaccuracy is a result of this, which is reflected in class hours for EFL learners.